Premature wear of the hip prosthesis as an early mechanical complication qualified for revision surgery – a rare case report and clinical implications - Sznajder, Wojciech; Tański , Wojciech (Journal of Education, Health and Sport, 2024)
Background: Mechanical complications of total hip arthroplasty (THA) are potential issues that may arise following the primary THA. Improper placement of THA can lead to misalignment of the joint axis, resulting in instability, pain, and walking difficulties. Among the relatively rare postoperative mechanical complications, premature wear of prosthesis components is included. This wear can lead to catastrophic prosthesis dislocation, necessitating surgical revision of the THA. Aim of the study: The aim of this paper is to present an intriguing case description of a patient with premature THA wear classified as an early postoperative mechanical complication, warranting revision THA surgery. The likely cause of premature wear of the implanted acetabular cup was excessive prosthesis use associated with intense physical activity and a high level of patient fitness. Care report: The paper presents the medical history and treatment course of a 33-year-old active patient who underwent uncemented left hip THA surgery due to diagnosed coxarthrosis caused by congenital dysplasia. After 5 years, premature wear of the implanted acetabular cup occurred. The likely cause was excessive prosthesis exploitation related to intensive physical activity and a high level of patient fitness. A year after the first revision surgery, THA dislocation occurred, resulting in the necessity of a second revision with replacement of the acetabular cup, polyethylene inserts and femoral head of the endoprosthesis. Summary: Premature wear of THA poses a significant clinical challenge. Functional limitations, associated with the loss of hip joint stability, lead to difficulties in performing basic activities, further decreasing the patient’s quality of life. It is also worth emphasizing that the treatment process for premature THA wear is associated with the possibility of surgical complications and a prolonged recovery period.